Penyusunan Standar Operasional Prosedur Peminjaman Sarana Prasarana di Yayasan Pendidikan Baabul Kamil - Nurdin Hadiansah, Nurdin Hadiansah; Abubakar, Rodlial Ramdhan Tackbir (Politeknik STIA LAN Bandung, 2024)
Facilities and infrastructure are an important part of providing education. In its implementation, borrowing infrastructure requires a procedure which is to prevent errors occurring in the work that can harm employees and the foundation. The object of this community service is the Baabul Kamil Jatinangor Education Foundation. This foundation does not yet have adequate SOPs in carrying out its duties. So this service aims to assist the Baabul Kamil Education Foundation in preparing Standard Operating Procedures (SOP), especially in borrowing infrastructure from the Baabul Kamil Education Foundation.